ANALISA HUKUM ATAS KEDUDUKAN KREDITUR LAIN DALAM UPAYA HUKUM KASASI PADA PERKARA KEPAILITAN (STUDI TERHADAP TIGA PUTUSAN MAHKAMAH AGUNG) - NUR ELFIRA NIRMALA POHAN (PREMISE LAW JURNAL, 2016)
Another creditor is a requirement to be met by an applicant who applies for bankruptcy before a court; it is a requirement stipulated in Article 2 paragraph (1) of the UUKPKPU (the Law on Bankruptcy and Suspension of Obligation for Debt Payment) which obliges the presence of two or more other creditors in applying for bankruptcy. In the development of bankruptcy cases, the other creditor occasionally refuses and objects to the debtor’s bankruptcy. The research used normative judicial method which was descriptive. An appeal by the other creditor who was not one of the parties involved in the first level court reflected a position equity between the other creditor and the bankruptcy applicant (the debtor themselves or the creditor) who were involved in the first level court. Keywords: Other Creditor, Appeal, Bankruptcy Law